2015
DOI: 10.2217/fon.15.265
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Selected Dermatological Toxicities in Cancer Patients Treated with MEK Inhibitors: A Comparative Systematic Review and Meta-Analysis

Abstract: Our meta-analysis has demonstrated that MEK inhibitor-based treatment is associated with an increased risk of all-grade and high-grade skin rash and acneiform dermatitis compared with control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The therapeutic use of kinase inhibitors and biological agents targeting kinase signaling pathways has introduced new toxicities in oncology clinics [ 5 ]. In particular, treatments that include EGFR inhibitors or MEK inhibitors typically associate with an increased risk of all-grade inflammatory skin rash characterized by papulo-pustular eruptions and acneiform dermatitis [ 13 , 14 ]. In our search for the molecular mechanisms underlying the pro-inflammatory and cytotoxic potential of EGFR inhibitors in the skin, we recently documented drug-induced activation of a type I interferon (IFN) innate immune response, with enhanced expression of the keratinocyte-specific IFN-κ, a number of anti-viral effectors including distinct members of the interferon-induced tetratricopeptide repeats (IFIT) family and immune mediators [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic use of kinase inhibitors and biological agents targeting kinase signaling pathways has introduced new toxicities in oncology clinics [ 5 ]. In particular, treatments that include EGFR inhibitors or MEK inhibitors typically associate with an increased risk of all-grade inflammatory skin rash characterized by papulo-pustular eruptions and acneiform dermatitis [ 13 , 14 ]. In our search for the molecular mechanisms underlying the pro-inflammatory and cytotoxic potential of EGFR inhibitors in the skin, we recently documented drug-induced activation of a type I interferon (IFN) innate immune response, with enhanced expression of the keratinocyte-specific IFN-κ, a number of anti-viral effectors including distinct members of the interferon-induced tetratricopeptide repeats (IFIT) family and immune mediators [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 One review of 14 trials of cancer patients on 3 MEK inhibitors reported the relative risk of acneiform dermatitis at 8.44 (95% confidence interval, 2.39-29.81; P = .0009). 4 This eruption does not always respond to traditional acne therapy with topical treatment and oral antibiotics. 2 Skin toxicities are considered an important cause for treatment interruption of MEK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of such improvements, MEK inhibitors have been associated with serious cytotoxicity [10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Treatment with MEK inhibitors can lead to serious iatrogenic responses [10,11]. Ocular toxicity seems to be associated with MEK inhibitors [12].…”
Section: Introductionmentioning
confidence: 99%